2013
DOI: 10.7897/2230-8407.04308
|View full text |Cite
|
Sign up to set email alerts
|

Typhonium Flagelliforme: A Multipurpose Plant

Abstract: Typhonium flagelliforme is a prominent plant candidate from aroid family, endowing various curative properties against a variety of illness and infections. This tropical plant found in damp, shady habitats and population of south east asian countries used it as alternative curative health supplement. Traditionally, this plant is used as a alternative remedy for cancer. Also, antibacterial and antioxidant activities are well established. This plant has shown promising results as a cough suppressant, which can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 12 publications
1
28
0
Order By: Relevance
“…As expected, the conductivity of PVA/CS solution declined from 1.69 to 1.04 mSÁcm 21 as the weight ratio of PVA/CS increased ARTICLE WILEYONLINELIBRARY.COM/APP from 1 : 1 to 4 : 1 because CS is anionic polyelectrolyte. As the charges carried by the jet increased, higher elongation forces were imposed to the jet under the electrical field.…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…As expected, the conductivity of PVA/CS solution declined from 1.69 to 1.04 mSÁcm 21 as the weight ratio of PVA/CS increased ARTICLE WILEYONLINELIBRARY.COM/APP from 1 : 1 to 4 : 1 because CS is anionic polyelectrolyte. As the charges carried by the jet increased, higher elongation forces were imposed to the jet under the electrical field.…”
Section: Resultssupporting
confidence: 75%
“…In order to investigate the interactions among PVA, CS, and ZrO 2 units, FTIR spectra measurements were taken ( Figure 5). In the FTIR spectrum of PVA [ Figure 5(a)], a characteristic peak of AOH stretching vibration was presented at 3378 cm 21 , and the AOH bending vibration was at 1432 cm 21 . The absorption peaks at 2937 and 1090 cm 21 were associated with CAH and CAO stretching vibrations, respectively, and 849 cm 21 was because of the CAC absorption peak.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in vitro study reported by Shin, et al displayed that administration of curcumin in ovarian cancer cells line (Siha cells) was able to activate cytochrome c and caspase3 and reduce up to 73% of ovarian cancer cell viability 23 . Mankaran and coworker also reported that administration of TP in cell cultures of human lung carcinoma (NCL-H23) was able to increase apoptosis detected by TUNNEL method 24 . Study was reported by Fuida showed that CZ oil has cytotoxic effects on NSCLC cell cultures characterized by apoptosis 25 .…”
Section: Discussionmentioning
confidence: 93%
“…[19][20][21] Poly(vinyl alcohol) (PVA), a water-soluble polyhydroxy polymer, has been widely investigated for biomedical applications because of its excellent electrospinnability, inherent nontoxicity, biocompatibility, biodegradability, and mechanical properties. [22][23][24][25][26][27] It is convenient to fabricate SPI/ PVA compound nanofibers by an electrospinning technique because both SPI and PVA exhibit hydrogen bonding. 28,29 To improve the properties of SPI/PVA compound nanofibers, we hybridized SiO 2 nanoparticles into the polymer matrix in our early work.…”
Section: Introductionmentioning
confidence: 99%